Developmental Changes in Task‐Induced Brain Deactivation in Humans Revealed by a Motor Task. Issue 6 (10th June 2019) - Morita, Tomoyo; Asada, Minoru; Naito, Eiichi
Abstract: Performing tasks activates relevant brain regions in adults while deactivating task‐irrelevant regions. Here, using a well‐controlled motor task, we explored how deactivation is shaped during typical human development and whether deactivation is related to task performance. Healthy right‐handed children (8–11 years), adolescents (12–15 years), and young adults (20–24 years; 20 per group) underwent functional magnetic resonance imaging with their eyes closed while performing a repetitive button‐press task with their right index finger in synchronization with a 1‐Hz sound. Deactivation in the ipsilateral sensorimotor cortex (SM1), bilateral visual and auditory (cross‐modal) areas, and bilateral default mode network (DMN) progressed with development. Specifically, ipsilateral SM1 and lateral occipital deactivation progressed prominently between childhood and adolescence, while medial occipital (including primary visual) and DMN deactivation progressed from adolescence to adulthood. In adults, greater cross‐modal deactivation in the bilateral primary visual cortices was associated with higher button‐press timing accuracy relative to the sound. The region‐specific deactivation progression in a developmental period may underlie the gradual promotion of sensorimotor function segregation required in the task. Task‐induced deactivation might have physiological significance regarding suppressed activity in task‐irrelevant regions. Furthermore, cross‐modal deactivation develops to benefit some aspects of task performance in adults.